Liderazgo transformacional y satisfacción laboral de los colaboradores de una PYME en Iquitos 2024 - Delgado Céspedes, Alcides Armando (2025)
This research aimed to determine how transformational leadership relates to job satisfaction among employees of an SME in Iquitos in 2024. A non experimental, cross-sectional, and basic design was used. The data collected through the questionnaire were reviewed to detect and correct errors. The sample consisted of 30 employees of an SME in Iquitos. The results showed that, regarding the transformational leadership variable, the majority of respondents strongly agreed (46.7%), while a certain percentage (33.3%) indicated agreement, 6.7% strongly disagreed, and only a small percentage responded disagree (6.7%) or neither agree nor disagree (6.6%). This indicates that, according to the established evaluation criteria, the perception of emotional intelligence is at a high level. In conclusion, regarding Transformational Leadership, the majority of respondents (46.7%) strongly agreed with the variable, indicating a positive perception of the leader's qualities, particularly their high level of emotional intelligence. This result suggests that employees perceive their leaders as effective in managing and understanding emotions within the work environment, which fosters a positive organizational climate and communication.